Positive imagery cognitive bias modification (CBM) and internet-based cognitive behavioral therapy (iCBT): A randomized controlled trial - Williams, Alishia D. (J Affect Disord, 2015)
BACKGROUND: Accruing evidence suggests that positive imagery-based cognitive bias modification (CBM) could have potential as a standalone targeted intervention for depressive symptoms or as an adjunct to existing treatments. We sought to establish the benefit of this form of CBM when delivered prior to Internet cognitive behavioral therapy (iCBT) for depression METHODS: A randomized controlled trial (RCT) of a 1-week Internet-delivered positive CBM vs. an active control condition for participants (N=75, 69% female, mean age=42) meeting diagnostic criteria for major depression; followed by a 10-week iCBT program for both groups. RESULTS: Modified intent-to-treat marginal and mixed effect models demonstrated no significant difference between conditions following the CBM intervention or the iCBT program. In both conditions there were significant reductions (Cohen׳s d .57–1.58, 95% CI=.12–2.07) in primary measures of depression and interpretation bias (PHQ9, BDI-II, AST-D). Large effect size reductions (Cohen׳s d .81–1.32, 95% CI=.31–1.79) were observed for secondary measures of distress, disability, anxiety and repetitive negative thinking (K10, WHODAS, STAI, RTQ). Per protocol analyses conducted in the sample of participants who completed all seven sessions of CBM indicated between-group superiority of the positive over control group on depression symptoms (PHQ9, BDI-II) and psychological distress (K10) following CBM (Hedges g .55–.88, 95% CI=−.03–1.46) and following iCBT (PHQ9, K10). The majority (>70%) no longer met diagnostic criteria for depression at 3-month follow-up. LIMITATIONS: The control condition contained many active components and therefore may have represented a smaller ‘dose’ of the positive condition. CONCLUSIONS: Results provide preliminary support for the successful integration of imagery-based CBM into an existing Internet-based treatment for depression.